Real-world assessment of attenuated dosing anti-PD1 therapy as an alternative dosing strategy in a high-income country (as defined by World Bank) - Low, Jia Li; Huang, Yiqing; Sooi, Kenneth; Chan, Zhi Yao; Yong, Wei Peng; Lee, Soo Chin; Goh, Boon Cher (Frontiers in Oncology, 2022)
Rising cost of oncological drugs pose a global challenge to patients, insurers and policy makers, with the leading drugs worldwide by revenue from immune checkpoint inhibitors (ICI). Despite its cost, ICI is marked as a paradigm shift, offering the potential of a long-term cure. To reduce cost, an attenuated dose of ICI based on pharmacological principles can be used while maintaining efficacy. This real-world study aims to examine the prescribing patterns, the effect of financial constraints and the outcomes in non-small cell lung cancer (NSCLC). All patients receiving palliative intent ICI treatment for advanced NSCLC between Jan 2014 and April 2021 in National University Hospital, Singapore were recruited. Demographics, prescription trends, factors affecting the prescription of attenuated dose ICI (AD ICI) versus standard dose ICI (SD ICI) and the effect of dose on survival outcomes, toxicities and costs were examined. Two hundred and seventy four received ICI. Majority of them were treated in first line setting. 162 (59%) of patients received AD ICI while 112 (41%) received SD ICI. Patients who did not have a supplemental private as-charged health insurance plan were more likely to have received AD ICI (OR: 4.53 (2.69-7.61)p<0.001). There was no difference in progression-free survival (PFS) and overall survival (OS) - adjusted HR 1.07 CI 0.76-1.50 p=0.697 and HR 0.95 CI 0.67-1.34 p=0.773 respectively, between patients who received AD versus SD ICI. A cost minimisation analysis evaluating the degree of cost savings related to drug costs estimated a within study cost saving of USD 7,939,059 over 7 years. Our study provides evidence for AD-ICI as a promising strategy to maximise the number of patients who can be treated with ICI. This has the potential to make significant economic impact and allow more patients to benefit from novel therapies.